Variance Analysis of Genus Ipomoea based on Morphological Characters - SURATMAN SURATMAN; DWI PRIYANTO; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2000)
The objective of this research was to find out the variability of morphological characters of genus Ipomoea, including coefficient variance and phylogenetic relationships. Genus Ipomoea has been identified consisting of four species i.e.Ipomoea crassicaulis Rob, Ipomoea aquatica Forsk., Ipomoea reptans Poir and Ipomoea leari. Four species of the genus took from surround the lake inside the campus of Sebelas Maret University, Surakarta. Comparison of species variability was based on the variance coefficient of vegetative and generative morphological characters. The vegetative characters observed were roots, steams and leaves, while the generative characters observed were flowers, fruits, and seeds. Phylogenetic relationship was determined by clustering association coefficient. Coefficient variance analysis of vegetative and generative morphological characters resulted in several groups based on the degree of variability i.e. low, enough, high, very high or none. The phylogenetic relationship showed that Ipomoea aquatica Forsk. and Ipomoea reptans Poir. have higher degree of phylogenetic than Ipomoea leari and Ipomoea crassicaulis Rob.Â© 2000 Jurusan Biologi FMIPA UNS SurakartaKey words: Ipomoea, morphological characters, coefficient variance, phylogenetic relationships